Mekanisme Pembentukan Peraturan Daerah Di Kabupaten Konawe (Tinjauan Yuridis Undang-Undang Nomor 12 Tahun 2011) - Hasim Hartono (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2019)
Establishment of Regional Regulation Mechanisms in Konawe under Law No. 12 The year 2011 can be seen through the elaboration of the stages of the formation of local regulations in general. Starting from the planning, preparation, preparation techniques, formulation, discussion, approval, promulgation, and to the dissemination of local regulations, which kententuanya is to make local regulations, among others, the discussion should be held publicly and academic texts as a basic foundation in making perturan area. Mechanism preparation of Regional Regulation Konawe start of stages: a) Preparation of the Draft Local Regulation Local Regulation at the Environment Council; b) Preparation of the Draft Regulation on Environmental Regional Local Government; c) Process for Obtaining Approval of Parliament; d) The process of approval and promulgation; e) Regional Gazette and Regional News. Factors Inhibiting Formation Implementation of Regional Regulations in Konawe under Law No. 12 The year 2011 is: internal factors (the Executive and Parliament) which comprises: a) Human Resources inadequate; b) Discipline. As for the external factors (people) are: a) The substance of the Community Idea Less Participation Right; b) Low Public Awareness to Participate. Establishment of legislation that is ideal in Konawe under Law No. 12 The year 2011 refers to the substance by regional regulations should contain the following principles: a) The principle of aegis; b) The principle of humanity; c) The principle of nationality; d) The principle of family; e) The principle kenusantaraan; f) The principle of unity in diversity; g) The principle of justice; h) The principle of equality in law and governance; i) The principle of order and legal certainty; j) The principle of balance, harmony and alignment; and k) other appropriate Principle substance Regional Regulations concerned. Design of Local Regulation shall able to describe the social problems. One way to explore this problem is to move the observation and research. Furthermore, it should involve the public more aware of environmental conditions that exist in a society.